2016
DOI: 10.1016/j.bbrc.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Off-target effect of the cPLA2α inhibitor pyrrophenone: Inhibition of calcium release from the endoplasmic reticulum

Abstract: Cytosolic phospholipase A2α (cPLA2α) mediates agonist-induced release of arachidonic acid from membrane phospholipid for production of eicosanoids. The activation of cPLA2α involves increases in intracellular calcium, which binds to the C2 domain and promotes cPLA2α translocation from the cytosol to membrane to access substrate. The cell permeable pyrrolidine-containing cPLA2α inhibitors including pyrrophenone have been useful to understand cPLA2α function. Although this serine hydrolase inhibitor does not inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We reported that pyrrophenone blocks ER calcium release induced by receptor stimulation but not by thapsigargin suggesting that ABHD2 regulates IP 3 -mediated ER calcium release pathway that couples to mitochondrial calcium uptake, and not pathways that control basal calcium release [22]. A study that directly relates to our findings showed that ABHD2 knockdown blocks hepatitis B virus propagation [47].…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…We reported that pyrrophenone blocks ER calcium release induced by receptor stimulation but not by thapsigargin suggesting that ABHD2 regulates IP 3 -mediated ER calcium release pathway that couples to mitochondrial calcium uptake, and not pathways that control basal calcium release [22]. A study that directly relates to our findings showed that ABHD2 knockdown blocks hepatitis B virus propagation [47].…”
Section: Discussionmentioning
confidence: 62%
“…KT195 inhibits by covalent, irreversible carbamoylation of the active site serine. We have uncovered a novel mechanism involving the serine hydrolase ABHD2 for regulating ER calcium release [18, 22]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations